Pengaruh Latihan Small Sided Games Terhadap Akurasi Passing di La Brava Futsal Club - Moch. Bagus Ariffudin; Made Pramono (Indonesian Journal of Kinanthropology (IJOK), 2021)
Background: This study aims to determine the effect of small sided games training on passing accuracy at La Brava Futsal Club Methods: This research uses descriptive quantitative research method T-test analysis method with two variables, namely: Small sided games practice and passing accuracy. The population in this study was the La Brava Futsal Club team, which consisted of 25 men. The sample uses proportional sampling technique because the researcher gets advice from the coach with a sample of 10 athletes who meet the criteria Results: The results of this study can be concluded that there are significant data in the pre test and post test with a mean of 7,700 and 7,500. And in the error man shows a significant pre-test 0.54 and post-test 0.48. Conclusions: The results of this study can be concluded that there are significant data in the pre test and post test with a mean of 7,700 and 7,500. And in the error man shows a significant pre-test 0.54 and post-test 0.48. As a result, it was found that the small field game training method for the accuracy of the operands of the training program needed to be further improved. Therefore, this research is expected to help coaches improve the accuracy of their passes.